2017
DOI: 10.21122/2220-9506-2017-8-4-55-62
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Electrophysical and Photoelectric Properties of Nanocomposite Polymers by the Modified Kelvin Probe

Abstract: At present for analysis of the homogeneity of materials properties are becoming widely used various modifications of a scanning Kelvin probe. These methods allow mapping the spatial distribution of the electrostatic potential. Analysis of the electropotential profile is not sufficient to describe any specific physical parameters of the polymer nanocomposites. Therefore, we use an external energy impact, such as light. Purpose of paper is the modification of the Kelvin scanning probe and the conduct of experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that such coatings have an antibacterial effect [7]. Many works are devoted to the modification of porous materials [7,13,25,26] confirm the positive effect of the gradual release of antibacterial additives. This allows for a longer antiseptic effect on bacteria and prevents possible complications in case of infection in the implantation area.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies have shown that such coatings have an antibacterial effect [7]. Many works are devoted to the modification of porous materials [7,13,25,26] confirm the positive effect of the gradual release of antibacterial additives. This allows for a longer antiseptic effect on bacteria and prevents possible complications in case of infection in the implantation area.…”
Section: Resultsmentioning
confidence: 86%
“…The electrical potential (EP) was measured using the contact potential difference (CPD) method. The nonvibrating CPD method based on the Kelvin scanning probe method was implemented on a specialized scanning unit (Belarusian National Technical University (Minsk, Belarus)) to measure the electrical properties of CP coatings [24,25]. For evaluation of the corrosion behavior of the CP coatings on titanium substrates Versa STAT MC system (Princeton Applied Research, Oak Ridge, TN, USA) was used.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…The response of the surface electrostatic potential of polymer materials to external mechanical action was found earlier in [8]. This study used matrix high-pressure polyethylene (LDPE) 12203-250 grade as samples.…”
Section: Resultsmentioning
confidence: 88%
“…First, understanding of polymer charge mechanisms is of significant practical interest, for example, in manufacturing antistatic and insulating materials, fiber production, polymer recycling, etc. [7] Second, there is now a large arsenal of methods for the study of surface electrostatic potentials, and new methods are constantly being developed that can clarify the existing theoretical positions [7,8,14].…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of the samples was investigated by scanning electron microscopy (SEM) on LEO EVO 50 electron microscope (Zeiss, Germany) equipped with an INCA-Energy 350 EDS analyser (Oxford Instruments, Abingdon, UK) in Nanotech Centre of Collective Use, ISPMS SB RAS. The electrical potential (EP) was measured using contact potential differences (CPD) techniques on a specialized scanning installation (Belarusian National Technical University (Minsk, Belarus)) to measure EP of the CP coatings [4].The coating thickness before modification was equal to 40-45 µm. Its surface morphology was characterized by the presence of numerous spherical structural elements of up to 10-30 µm with pores.…”
mentioning
confidence: 99%